Compliance with inhaled asthma medication in preschool children. Issue 12 (December 1995) - Gibson, N A; Ferguson, A E; Aitchison, T C; Paton, J Y
Abstract : BACKGROUND--Previous studies have shown poor compliance with regular drug therapy in children and adults with asthma. In preschool children the parents supervise and are responsible for drug administration, but little is known of compliance in this group. In addition, there are few data on the patterns of drug use of inhaled prophylactic asthma therapy or of the relation between compliance and symptom control. A study was undertaken to address these issues with the hypothesis that parental supervision would result in good compliance. METHODS--The subjects were 29 asthmatic children aged 15 months to five years already established on inhaled prophylactic medication delivered through a large volume spacer. The prescribed drug regimens varied between subjects. This was an observational study using an electronic inhaler timer device to record the date and time of each actuation of the aerosol canister. Diary cards were used for parallel recording of symptoms and parentally reported compliance with a drug regimen. RESULTS--Variable and generally poor compliance was demonstrated with a median of 50% of study days with full compliance (subject range 0-94%) and an overall median of 77% of prescribed doses of therapy taken during the study period. No relation was found between frequency of prescribed regimen and good compliance. Day care was associated with poorer compliance. No relation between good compliance and low symptom scores was found. CONCLUSION--Compliance with inhaled prophylactic therapy is poor in preschool children with asthma whose medication is administered under parental supervision.